Legal Perspective Regarding the Authority of the Police for Confiscation of Evidence of Traffic Violations at Labuhanbatu Police - Lola Sefriany Pasaribu; Bernat Panjaitan; Nimrot Siahaan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This Study aim for analyze Perspective law About Authority Police to Foreclosure Goods Proof Violation Police Traffic Labuhanbatu. This Study characteristic Normative - Empirical that is method combined research element law normative and supported with data or element empirical. This Method study is implementation provision from law normative (law) for incident law that happened in the middle society. The benefits will accepted from results study This is For now and use study This as basis and theory in matter know and analyze Perspective Law About Authority Police To Foreclosure Goods Proof Violation Police traffic Labuhanbatu, study study this is also expected can help the Enforcers law specifically Police Republic of Indonesia For now and strengthen authority in handle Violation Accompanied traffic with foreclosure Goods Evidence. Research results show that kindly Law Party Police the Republic of Indonesia is authorized do foreclosure goods proof Violation Traffic, This As Proof exists Violation So cross done driver vehicle motorized as has been arranged in Legislation.